Assessment of Driver Distraction at Work Zones with Portable Rumble Strip Deployments in Texas. Issue 3 (March 2023) - Ullman, Gerald L.
The objective of this research was to assess the extent of distracted driving occurring on roadways in Texas, U.S., as drivers approach a work zone and the extent to which portable rumble strips (PRS) may influence those rates. The research team utilized direct field observations of drivers approaching work zones at several Texas work zones. At each work zone, team members positioned themselves near the location of the upstream set of PRS. Team members also collected observational data at a second location downstream from that initial PRS location. The results of the field studies showed that nearly one in five motorists are visually distracted in some manner while driving as they approach a work zone. The studies also showed that this rate of visual distraction decreased at distances closer to the work zone. Observations of distracted drivers as they passed over the PRS indicate that at least some of that decrease in distraction over distance was because of the presence of the PRS. Data were not sufficient to determine conclusively how long the distraction-reducing effects of PRS last. However, data from one site suggest that the effect was limited to the first 1, 500 ft after traversing the PRS.